Profit Opacity, Investor Legal Protection and Cost of Capital: A Conceptual Framework - Sriwidharmanely Sriwidharmanely; Herawansyah Herawansyah; Danang Adi Putra (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
This paper aims to develop a conceptual framework that investigates and provides a systematic understanding of the impact of long opacity and legal protection on investors on the cost of capital. This study refers to the literature related to earnings opacity, investor legal protection and the cost of capital to ascertain the impact of profit opacity and investor legal protection on the cost of capital and the mediating role of profit opacity on the relationship between legal protection of investors and the cost of capital. This conceptual framework describes the process of congruence between earnings opacity and investor legal protection as an antecedent and consequent to the cost of capital, as well as the mediating role of earnings opacity. The results of the literature review show three propositions. This framework provides an opportunity for seekers and practitioners to further investigate the effect of profit opacity on the cost of capital and the mediating role of this profit opacity in the relationship between investor legal protection and the cost of capital..